Strategies to reduce academic stress in postgraduate students in the distance education modality in times of COVID-19 - De Los Angeles Sanchez-Trujillo, Maria (2022)
The current context of a pandemic associated with a new remote educational modality has generated various effects on the world population. University students, and specifically postgraduate students, face various challenges to adapt to this new reality, which could generate certain levels of academic stress. This research of mixed nature sought, first, to determine the main frequencies of the dimensions of academic stress in 67 students of the master's degree in Education of a private university of Lima for which the Inventory of Academic Stress SISCO SV adapted to this context was applied. Secondly, it aimed to propose and evaluate strategies aimed at improving the psychological well-being of these students based on a focus group made to the students. In the initial findings, certain stressors perceived by the students were identified, such as the overload of tasks and works, the manner of evaluation of the teachers, and the perception about the limited time to do the works. In addition, among the most recurrent symptoms, are chronic fatigue, drowsiness or increased need for sleep, restlessness, and anxiety. From the application of strategies of an emotional and academic nature, there was an improvement in the perception declared by the students, which favored their psychological well-being.